Experimental Investigation on The AC Breakdown Strength of Air Under Various Uniformities - Jaizan Hadi, Batrisyia Balqis; Kamarudin, Muhammad Saufi (Evolution in Electrical and Electronic Engineering, 2022)
High Voltage AC (HVAC) is widely used in power systems, especially in transmission and distribution systems. Those systems use a very high or extra high voltage to transmit the power from the power generation to the consumer. To ensure that the power delivered to the consumer is efficient, all equipment involved such as the generator and transformer must have good insulation and can withstand high electrical stress and pressure. This insulation is important as protection to the equipment from suffering severe damage due to high voltage and current. Hence an investigation and an experiment were performed by using air as insulation. The experiment was performed based on the TERCO document catalog that provides the procedure and equipment list. In this project, there are five types of electrode pairs that have been used such as sphere-sphere, rod-rod, rod-sphere, sphere-plane and rod-plane with different gap distances from 0.5 cm to 3.0 cm.  This experiment was conducted in an HV laboratory to observe the breakdown voltage before using Finite Element Method Magnetics 4.2 (FEMM 4.2) software to obtain the electric field intensity, maximum electric field and field utilization factor for each pair of electrodes. There is some calculations were involved to obtain another parameter. The result such as breakdown voltage of air, distance gap and maximum electric field relationship were discussed in this project as well as the relationship between field utilization factor and gap distance. After all the analysis and discussion, sphere-sphere electrodes were found to be the best electrode pairs compares to others due to their high breakdown voltage which is 88.50 kV, low maximum electric field (Emax = 35.12 kV/cm) and has highest field utilization factor, 0.84 all at gap distance 3.0 cm.